Nonlocal effects in the nucleus-nucleus fusion cross section - Galetti, D. [UNESP]; Cĝndido Ribeiro, M. A. [UNESP] (American Physical Society (APS), 1994)
Effects of the nonlocality of factorizable potentials are taken into account in the calculation of nucleus-nucleus fusion cross section through an effective mass approach. This cross section makes use of the tunneling factor calculated for the nonlocal barrier, without the explicit introduction of any result coming from coupled channel calculation, besides the approximations of Hill-Wheeler and Wong. Its new expression embodies the nonlocal effects in a factor which redefines the local potential barrier curvature. Applications to different systems, namely, O16+59Co, O16,18+58,60,64Ni, and O16,18+63,65Cu are presented, where the nonlocal range is treated as a free parameter. © 1994 The American Physical Society.